Enhancing Arabic Speaking Skills through Short-Phrase Memorization in an Islamic Boarding School - Lutfi zarkasi (Al-Muhawaroh: Jurnal Pendidikan Bahasa Arab, 2025)
This study examines the effectiveness of the Short-Phrase Memorization Method in enhancing Arabic speaking skills among students at Ma’had al-Akhlāq al-Karīmah, Kulon Progo, Indonesia. A quantitative experimental design employing a pre-test–post-test control group was used. Fourteen boarding students were purposively selected and assigned to an experimental group receiving short-phrase-based instruction and a control group taught through conventional vocabulary memorization. Data were collected through speaking tests, classroom observation, and interviews. The findings reveal a statistically significant difference between the post-test scores of the experimental and control groups (t = 5.691, p < .01), indicating the superior effectiveness of phrase-based instruction. The experimental group showed substantial improvement in fluency, accuracy, and confidence, while the control group demonstrated limited progress. Qualitative observations further confirmed increased learner engagement, participation, and motivation throughout the intervention. These results support cognitive chunking theory and communicative language teaching principles, suggesting that learning language in functional units facilitates automaticity in speech production. The study concludes that short-phrase memorization constitutes a viable and pedagogically sound strategy for improving Arabic oral proficiency in Islamic boarding school contexts. Future research is recommended to extend the intervention to larger samples and explore integration with technology-enhanced instruction.